2015
DOI: 10.1109/tdmr.2015.2498310
|View full text |Cite
|
Sign up to set email alerts
|

Charge Trapping and Decay Mechanism in Post Deposition Annealed Er<sub>2</sub>O<sub>3</sub> MOS Capacitors by Nanoscopic and Macroscopic Characterization

Abstract: In this paper, the charge trapping and decay mechanism is investigated in post deposition rapid thermal anneal (RTA) and furnace anneal (FA) erbium oxide (Er 2 O 3 ) ultrathin films by Kelvin probe force microscopy (KPFM) technology. The trap density is calculated by the contact potential difference measurements obtained from KPFM. Furthermore, it is compared with the trap density calculated from the electrical measurements for Er 2 O 3 MOS capacitors to give an insight on the reliability of KPFM for trap dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Figure 11 shows the result of a second experiment performed in another pristine device. In this second case initially 3.20x10 12 3.01x10 12 3.34x10 12 3.50x10 12 Figure 8. Comparison between experimental C-V curves (ticks) and simulation results of the reference device (dashed lines).…”
Section: B Open Loop Actuation With Constant Voltages: Observation Omentioning
confidence: 97%
“…Figure 11 shows the result of a second experiment performed in another pristine device. In this second case initially 3.20x10 12 3.01x10 12 3.34x10 12 3.50x10 12 Figure 8. Comparison between experimental C-V curves (ticks) and simulation results of the reference device (dashed lines).…”
Section: B Open Loop Actuation With Constant Voltages: Observation Omentioning
confidence: 97%
“…Also, dominant loss due to shallow/interface traps rather than deep‐level/bulk traps indicates the formation of smooth large‐area Cu‐MOCs thin films with minimal uniformities aligning suitably with discussion in Section 2.1. At high frequencies, both capacitance and conductance measurements are affected by series resistance; [ 58 ] hence series resistance corrected (blue curve) and noncorrected (red curve) normalized G–V characteristics are shown in (Figure S6, Supporting Information) for Al/Cu‐MOCs/Si structures. The series resistance corrected conductance G C is extracted from C–V characteristics given by relation (equation S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 16,54,55,57,106 ] Liu and coworkers explored the effect of the HfO 2 thickness, postdeposition annealing temperature, and charge retention temperature on the vertical and lateral charge dissipation by KPFM. [ 16,54,106 ] In addition, the trapped charge properties of a ferroelectric film, [ 56 ] a fluorocarbon layer, [ 87 ] sapphire surfaces, [ 107 ] a double barrier CeO 2 /Si/CeO 2 /Si structure, [ 90 ] and undoped and copper‐doped zinc oxide (ZnO:Cu) films [ 108 ] have also been investigated by EFM/KPFM. Wong et al detected the surface potential of trapped charges for undoped and copper‐doped zinc oxide films using KPFM.…”
Section: The Properties Of Trapping Charges For Different Materials Bmentioning
confidence: 99%
“…The decay mechanisms have been reported, such as neutralizing the part‐trapped charges of an electret by attraction of the environmental charges, [ 2,47,78,104 ] the water dipoles and adsorbed water, [ 46,47 ] bulk space charge motion, [ 122 ] self‐repulsion, [ 47,122 ] Coulombic interaction, [ 52 ] and thermal diffusion. [ 47 ] Some researchers reported that the vertical charge leakage acted as a dominant role of charge loss with respect to lateral charge redistribution for HfO 2 , [ 106 ] Er 2 O 3 , [ 54 ] and Al 2 O 3 films, [ 55 ] while the cancellation of lateral surface conduction enhanced the charge retention ability. [ 46,123 ] The nanocrystal density will affect the retention properties of trapped charges when the nanocrystals are embedded in a silicon matrix.…”
Section: The Mechanism Of Injection and Decaymentioning
confidence: 99%
See 1 more Smart Citation